PENGARUH PEMBINAAN KEPALA SEKOLAH DAN KOMPENSASI TERHADAP KINERJA GURU NON PNS PADA SMP SWASTA DI SEKTOR I KABUPATEN INDRAMAYU - Rahmawati, Eti (Edum Journal, 2019)
The formulation of the issues raised in this research is: Is there any influence of headmaster and compensation on the performance of non-civil servant teachers in private junior high school in Sector I of Indramayu Regency. The purpose of this research is to analyze the influence of principal guidance on teacher performance and compensation on teacher performance, and the influence of principal guidance and compensation simultaneously on the performance of non-civil servant teachers in private sector SMP in Sector I Kabupaten Indramayu. The method used is descriptive method with a quantitative approach that uses simple and multiple regression analysis. The result of this research is there is positive and significant influence partially between each independent variable that is principal guidance and compensation to dependent variable that is teacher performance, and there are positive and significant influence between principal coaching variable and compensation simultaneously to performance non civil servant teachers at private junior high schools in Sector I Kabupaten Indramayu. This research is kind of correlation because to know the relation of principal guidance variable (X1), compensation (X2) and teacher performance (Y). While the data collection using questionnaires and analyzed using single regression and multiple regression. Hypothesis testing result obtained by R square value equal to 0,162 indicate that there is influence positively and significant coaching principal and compensation simultaneously to teacher performance equal to 16,2%, the rest from other factor outside of both variable. The principal can maintain and improve the teacher's reproduction by continuing to conduct regularly, the principal can also increase teacher training activities through field trips, attend seminars or headmaster training and try to be role models for teachers in schools.